2010
DOI: 10.1002/qj.528
|View full text |Cite
|
Sign up to set email alerts
|

Doppler lidar measurements of oriented planar ice crystals falling from supercooled and glaciated layer clouds

Abstract: The properties of planar ice crystals settling horizontally have been investigated using a vertically pointing Doppler lidar. Strong specular reflections were observed from their oriented basal facets, identified by comparison with a second lidar pointing 4 • from zenith. Analysis of 17 months of continuous high-resolution observations reveals that these pristine crystals are frequently observed in ice falling from mid-level mixed-phase layer clouds (85% of the time for layers at −15 • C). Detailed analysis of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 62 publications
13
81
0
1
Order By: Relevance
“…The latter appear in ∼20% of ice clouds layers between −10°C and −15°C globally [Hogan et al, 2004], i.e., in the temperature range where the present study found the highest concentration of oriented crystals. Recent ground-based observations suggest that supercooled layers play an important part in the formation of planar ice crystals susceptible to orientation [Westbrook et al, 2010], at least at midlatitudes. It is unclear at this point how many supercooled layers appear in the CALIOP data set and how they relate to crystal orientation, as techniques for reliable identification of in-cloud phase variation are still experimental, but it is a question that needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter appear in ∼20% of ice clouds layers between −10°C and −15°C globally [Hogan et al, 2004], i.e., in the temperature range where the present study found the highest concentration of oriented crystals. Recent ground-based observations suggest that supercooled layers play an important part in the formation of planar ice crystals susceptible to orientation [Westbrook et al, 2010], at least at midlatitudes. It is unclear at this point how many supercooled layers appear in the CALIOP data set and how they relate to crystal orientation, as techniques for reliable identification of in-cloud phase variation are still experimental, but it is a question that needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Planar crystal growth occurs predominantly in the −12°C to −18°C range [Fukuta and Takahashi, 1999], thus present results reinforce the hypothesis that oriented crystals are mostly planar, with in-cloud vertical motions and sedimentation explaining why oriented crystals are detected in a slightly wider temperature range. The higher detection of oriented crystals just above cloud base requires enhanced planar crystals in that area, which can be explained either by (1) sedimentation from a higher, midcloud supercooled layer where crystals are rapidly nucleated (as described by Westbrook et al [2010]) or (2) ascending air from turbulence near the ice-subsaturated cloud base [Miloshevich and Heymsfield, 1997] leading to the nucleation of new pristine ice crystals at colder temperatures higher within the cloud. Future work should investigate the importance of these mechanisms, by (1) studying levels of supersaturation in and around warm and cold ice clouds, which might influence crystal growth and shape [Spichtinger et al, 2004] and (2) correlate supercooled layers with oriented crystals on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…Combined lidar and dual polarization radar observations and Ka-band cloud radar depolarization ratio observations in winter layer clouds containing pristine planar ice indicate that crystals can fall with orientations that are very nearly horizontal [Matrosov et al, 2005;Westbrook et al, 2010]. From a more theoretical perspective, Klett [1995] has argued that even for high kinetic eddy dissipation rates of 0.1 m 2 s −3 (similar to what might be observed in a convective cloud), based on an inertial subrange model for turbulence, the calculated average tilt of branched plates larger than about 0.1 mm should be expected to be no more than about 10 ∘ .…”
Section: 1002/2015gl064040mentioning
confidence: 99%
“…In the case of planar planes of horizontally oriented ice crystals, specular reflection appears (e.g. Westbrook et al, 2010;Sassen and Benson, 2001), which results in a high backscatter coefficient and a low depolarization ratio. Specular reflection occurs under conditions where large planar ice crystals are formed and align horizontally during sedimentation.…”
Section: Lidar Observationmentioning
confidence: 99%